2020
DOI: 10.1038/s41440-020-0476-3
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of ACE2 induces overstimulation of the renin–angiotensin system in COVID-19: should we block the renin–angiotensin system?

Abstract: Severe acute respiratory syndrome coronavirus 2 is the cause of the ongoing coronavirus disease-19 (COVID-19) pandemic. Mortality is mainly due to acute respiratory distress syndrome (ARDS) [1]. High blood pressure appeared to be an independent factor for severity in patients with COVID-19 [2, 3]. The renin-angiotensin system (RAS) is a hemodynamic and biological system that regulates blood pressure, plasma potassium, and the stability of pulmonary epithelial membranes (Fig. 1) [4]. In this system, two antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 24 publications
0
108
0
4
Order By: Relevance
“…This hypothesis is further supported by recent electron microscopic studies that have demonstrated the presence of viral inclusion particles within the endothelium, and viral RNA detection in cerebrospinal fluid [ 41 , 42 ]. Second, entry of the SARS-CoV-2 virus into cells results in marked reduction in ACE-2 levels [ 43 ]. Since this protein usually catalyzes conversion of angiotensin II to counter-regulatory angiotensin 1-7 [ 44 , 45 ], reduction in its levels results in enhanced and unopposed effects angiotensin II via the ACE-angiotensin II-AT1 receptor axis [ 43 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is further supported by recent electron microscopic studies that have demonstrated the presence of viral inclusion particles within the endothelium, and viral RNA detection in cerebrospinal fluid [ 41 , 42 ]. Second, entry of the SARS-CoV-2 virus into cells results in marked reduction in ACE-2 levels [ 43 ]. Since this protein usually catalyzes conversion of angiotensin II to counter-regulatory angiotensin 1-7 [ 44 , 45 ], reduction in its levels results in enhanced and unopposed effects angiotensin II via the ACE-angiotensin II-AT1 receptor axis [ 43 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from lungs, ACE2 was also expressed in the extrapulmonary surface. SARS-CoV-2 enters the cell by membrane diffusion and slows down the regulation of ACE2 receptor (Qian et al, 2013;Silhol et al, 2020). TMPRSS2 based entry of SARS-CoV-2 has been observed when cleavage of the S1/S2 site is mediated by furin in the virus-infected cell (Coutard et al, 2020).…”
Section: Host Factorsmentioning
confidence: 99%
“…Patients with existing cardiovascular diseases face a higher risk of COVID-19 (Kuno et al, 2020;Li et al, 2020b;Richardson et al, 2020b). In patients with cardiovascular diseases, diabetes mellitus, and hypertension treated with ACE inhibitors and ARBs, the expression of ACE2 contributes to worsening the prognosis of COVID-19 patients (Birnbaum, 2020;Cannata et al, 2020;Fosbøl et al, 2020;Mackey et al, 2020;Pirola and Sookoian, 2020;Silhol et al, 2020). In contrast, several recent clinical studies provide evidence that ACE inhibitors and ARBs may be beneficial in COVID-19 patients with hypertension and, hence, recommend continuing ACE inhibitors and ARBs (Kang et al, 2020;Mackey et al, 2020).…”
Section: Introductionmentioning
confidence: 99%